2009
DOI: 10.1097/ta.0b013e3181af6ef4
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Predictors of Need for Angiographic Embolization After Traumatic Renal Injury

Abstract: Background: Although the American Association of the Surgery for Trauma Organ Injury Scale is the gold standard for staging renal trauma, it does not address characteristics of perirenal hematomas that may indicate significant hemorrhage. Angiographic embolization has become well established as an effective method for achieving hemostasis. We evaluated two novel radiographic indicators-perirenal hematoma size and intravascular contrast extravasation (ICE)-to test their association with subsequent angiographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…These investigators reviewed AAST OIS grade, complexity of laceration, hematoma size, continuity of Gerota’s fascia, and presence of ICE and suggested angiography be performed with presence of ICE, but in the absence of ICE, only be considered when hematoma size is 25 mm or larger. Nuss et al [16] reviewed CT images of 52 patients who underwent AE for grade III–IV renal trauma, noting that perirenal hematoma size >40 mm and ICE provided for two readily identifiable CT features associated with the need for embolization. Other measurements, including hematoma area ≥128 cm 2 , hematoma/kidney ratio ≥2.75, hematoma/kidney diameter ≥76.5 cm 2 , were associated with need for embolization.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators reviewed AAST OIS grade, complexity of laceration, hematoma size, continuity of Gerota’s fascia, and presence of ICE and suggested angiography be performed with presence of ICE, but in the absence of ICE, only be considered when hematoma size is 25 mm or larger. Nuss et al [16] reviewed CT images of 52 patients who underwent AE for grade III–IV renal trauma, noting that perirenal hematoma size >40 mm and ICE provided for two readily identifiable CT features associated with the need for embolization. Other measurements, including hematoma area ≥128 cm 2 , hematoma/kidney ratio ≥2.75, hematoma/kidney diameter ≥76.5 cm 2 , were associated with need for embolization.…”
Section: Discussionmentioning
confidence: 99%
“…42 Nuss et al also reported that the size of the perirenal haematoma and the presence of intravascular contrast extravasation were associated with the need for angiographic embolisation. 43 There is an expanding role for renal arterial embolisation and in some situations, the procedure can be performed intraoperatively in cases of poly-trauma where intraperitoneal injuries are repaired during laparotomy and the associated renal injury is managed by interventional radiology techniques.…”
Section: Angiography and Embolisationmentioning
confidence: 99%
“…Anjiyografinin başlıca endikasyonları, aktif hemoraji, psödoanevrizma ve vasküler fistüller için embolizasyontur (26) . Renal hasarın derecesinin ilerlemesi anjioembolizasyonun ilk denemedeki başa-rısını düşürür ve yine müdahale gereksinimini arttırır.…”
Section: Tedaviunclassified